Scientific Opinion on the assessment of the control measures of the category A diseases of Animal Health Law: African Horse Sickness. (3rd February 2021) - ; Nielsen, Søren Saxmose; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Depner, Klaus; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, José Luis; Gortázar Schmidt, Christian; Herskin, Mette; Michel, Virginie; et al.
Abstract: EFSA received a mandate from the European Commission to assess the effectiveness of some of the control measures against diseases included in the Category A list according to Regulation (EU) 2016/429 on transmissible animal diseases ('Animal Health Law'). This opinion belongs to a series of opinions where these control measures will be assessed, with this opinion covering the assessment of control measures for African Horse Sickness (AHS). In this opinion, EFSA and the AHAW Panel of experts review the effectiveness of: (i) clinical and laboratory sampling procedures, (ii) monitoring period and (iii) the minimum radius of the protection and surveillance zone, and the minimum duration of measures in these zones. The general methodology used for this series of opinions has been published elsewhere; nonetheless, specific details of the transmission kernels used for the assessment of the minimum radius of the protection and surveillance zones are shown. Several scenarios for which these control measures were assessed were designed and agreed prior to the start of the assessment. In summary, sampling procedures described in the diagnostic manual for AHS were considered efficient for all Equidae considering the high case fatality rate expected. The monitoring period (14 days) was assessed as effective in every scenario, except for those relating to the epidemiological enquiry where the risk manager should consider increasing the monitoring period, based on the awareness of keepers, environmental conditions and the vector abundance in the region. The current protection zone (100 km) comprises more than 95% of the infections from an affected establishment. Both the radius and duration of the zones could be reduced, based on local environmental conditions and the time of year of the first index case. Recommendations provided for each of the scenarios assessed aim to support the European Commission in the drafting of further pieces of legislation relating to AHS.